Multicultural poetics : re-visioning the American canon - Parmar, Nissa (SUNY series in multiethnic literature., 2018)
Multicultural Poetics provides a new perspective on American poetry that will contribute to the evolution of contemporary critical practice. Nissa Parmar combines formalist analysis with cultural studies theory to trace a lineage of hybrid poetry from the American Renaissance to what Marilyn Chin deemed America's "multicultural renaissance," the blossoming of multicultural literature in the 1980s and 1990s. This re-visionary literary history begins by analyzing Whitman and Dickinson as postcolonial poets. This critical approach provides an alternative to the factionalism that has characterized twentieth-century American poetic history and continues to inform literary criticism in the twenty-first century. Parmar uses a multiethnic, multigender method that emphasizes the relationship between American poetic form and cultural development. This book provides a new approach by using hybridity as the critical paradigm for a study that groups multiethnic and emergent authors. It thereby combats literary ghettoization while revealing commonalities across American literatures and the cross-fertilization that has informed their development.